Political participation and trends in university students: The case of the University of Chile - Carrasco Azzini, Giovanni (Última Década, 2020)
For years in our country, the trend and political participation of university students was key to the various governments that took place until 1973. The University of Chile, in both the first and largest higher education institution in the country, was always seen with a special interest, even stating that «what happened on the date, happened in Chile». However, once started the authoritarian regime in our country, the relationship defined above is no longer such until today. This research, exploratory qualitative aims to analyze the possible relationships between national policy and university policy, and explain the reasons for which, apparently, the political orientation of the student organizations at the University of Chile and do not reflect reality national